Sleep in the Military Promoting Healthy Sleep Among U.S. Servicemembers - Troxel, Wendy M. (RAND Corporation, 2015)
Given the unprecedented demands on the U.S. military since 2001 and the risks posed by stress and trauma, there has been growing concern about the prevalence and consequences of sleep problems. This first-ever comprehensive review of military sleep-related policies and programs, evidence-based interventions, and barriers to achieving healthy sleep offers a detailed set of actionable recommendations for improving sleep across the force.